TOBACCO DIVERSITY IN INDONESIA - Djajadi Djajadi (The East Java Biological Society, 2015)
Tobacco variants in Indonesia are very diverse which can be identified from their morphology or their characteristics. This is related to tobacco long adaptation in different agro ecology of plantation areas which spread out at 15 provinces, from dry to irrigated land and from low land to high land areas. Tobacco has been introduced in Indonesia for more than four centuries and mostly used as cigarette. This commodity and its products are still economi-cally important for government and farmer income. It contributes in government income which reached up to 114 trillion rupiahs and farmer income up to 70% in 2014. Tobacco diversity in Indonesia can be grouped according to their growing season and their usage in cigarette blending. Tobaccos which grown at the end of wet season and harvested in dry season are called Voor Oogst tobaccos, otherwise tobaccos which grown at dry season and harvested in wet season are called Na Oogst tobaccos. Based on their usage, tobaccos are categorized as main ingredients for kretek cigarette, Rolled Your Own (RYO) cigarette, and cigar industries.